Partisipasi Masyarakat dan Peran Mahasiswa dalam Meningkatkan Kebersihan Lingkungan Kampus - Sirojuddin Abror; Muhammad Aqil Permana Putra; Kurnia Wijaya; Febrian Dirgantara; Novritsar Hasitongan Pakpahan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Campus cleanliness is a crucial aspect in creating a healthy and comfortable learning environment. Community participation and student participation are essential in improving campus cleanliness. This community service activity aims to determine how community participation and student participation contribute to improving campus cleanliness. The method used is Participatory Action Research (PAR). Data collection techniques include observation and interviews. The results indicate that community participation and student participation can improve campus cleanliness through activities such as mutual cooperation (gotong royong), cleanliness campaigns, and environmental education. This activity is expected to contribute to the development of strategies for improving campus cleanliness sustainably.